A systematic review of the effectiveness of psychological approaches in the treatment of sex offenders with intellectual disabilities. Issue 1 (23rd March 2017) - Jones, Emma; Chaplin, Eddie
Abstract : Background: Despite considerable advance and growth in the evidence base for psychological interventions as treatment for sex offenders with intellectual disabilities (ID), there remains limited evidence to support their effectiveness. This systematic review seeks to evaluate the effectiveness of psychological interventions on reducing reoffending rates for sex offenders with ID. Methods: A search of ten electronic databases, grey literature and reference lists was conducted using PRISMA methodology. Results: A number of studies appeared to establish positive treatment outcomes, demonstrated by improvements in attitudinal change, victim empathy and sexual knowledge. However, reductions in sexual reoffending during the follow‐up period were not consistent across the studies. No studies with an adequate control comparison were identified during the search. Conclusions: The current review provides limited evidence on the effectiveness of psychological interventions for sex offenders with ID, while also highlighting the need for further research.